The Effect of Governance, Education, and Economic Conditions on GDP in ASEAN - Phandy, Angel; Yosal, Calista; Wilar, Felicia Brilianti; Putri, Telysia Tony; Adha, Wirdah Nur; Maichal, Maichal (Universitas Muhammadiyah Yogyakarta, 2026)
This study investigates the effect of governance, education, and economic conditions on GDP in eight ASEAN countries—Indonesia, Malaysia, Thailand, Singapore, the Philippines, Vietnam, Laos, and Cambodia—during the period 2006–2020. Governance is represented by the Corruption Perceptions Index and Ease of Doing Business indicators, while education and inflation are¬¬ used to reflect human capital and economic stability, respectively. Data were obtained from the World Bank and Transparency International. Using panel data regression, the study combined cross-sectional and time-series data. Based on the Chow test, the Common Effect Model (CEM) was identified as the most appropriate. Due to classical assumption violations, robust standard errors were employed to ensure reliable estimates. The results show that Ease of Doing Business, education, and inflation significantly influence GDP. An improved business environment and higher educational attainment contribute to economic growth, while controlled inflation ensures macroeconomic stability. Meanwhile, corruption showed no significant impact on GDP. The findings highlight the importance of improving governance quality, expanding access to quality education, and maintaining stable inflation to support sustained economic growth in ASEAN.